Le nuove frontiere della catalisi ecosostenibile: un viaggio, dai catalizzatori omogenei alla fotocatalisi, ripercorrendo le tappe storiche più rilevanti per il suo sviluppo - Crucianelli, Marcello; Di Nicola, Nicola (Chimica nella Scuola, 2025)
Catalytic processes are behind many chemical reactions, both industrial and non-industrial. Since the 1990s, with the rise of Green Chemistry concept and its 12 principles for making chemistry more sustainable and environmentally friendly, scientists around the world have been increasingly interested in understanding the central role of catalysis. Understanding how catalysts work is very important since they help chemical reactions to take place faster and more efficiently, using less energy and producing less waste. This short review covers the scientific advancements during the past 30 years which allowed the development of catalytic processes in a more eco-friendly way. All this, starting from homogeneous catalysis, moving through hybrid multifunctional catalysts, and ending with photocatalysis, by tracing a brief history of catalysis, its advancement and the most relevant Nobel Prizes specifically awarded to it.